2018
DOI: 10.3390/app8091626
|View full text |Cite
|
Sign up to set email alerts
|

Properties Analysis of Oil Shale Waste as Partial Aggregate Replacement in Open Grade Friction Course

Abstract: Open graded friction course (OGFC) is a high permeable mixture used to reduce noise, improve friction. However, limitations with the use of OGFC are due to the relatively low strength and stiffness. Therefore, investigating environmental and economic benefits, as well as service life of OGFC technology is the future of the pavement. In this study, a new modified OGFC (SM-OGFC) was prepared by replacing the fine aggregate below 4.75 mm in OGFC with the oil shale waste (OSW), and the silane coupling agent modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…As described above, a complete freeze-thaw cycle is completed. After 5 freeze-thaw cycles, damaged specimens were collected for Marshall test according to Chinese standards GB/T0709-2011 [36]. The raveling resistance properties of asphalt mixture was analyzed through standard Cantabro test, and permeability was evaluated by constant head permeability test.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As described above, a complete freeze-thaw cycle is completed. After 5 freeze-thaw cycles, damaged specimens were collected for Marshall test according to Chinese standards GB/T0709-2011 [36]. The raveling resistance properties of asphalt mixture was analyzed through standard Cantabro test, and permeability was evaluated by constant head permeability test.…”
Section: Methodsmentioning
confidence: 99%
“…Higher water absorption may lead to poor water stability of OSW in the pavement material application. In a previous study, the standard immersion Marshall test showed that utilization of oil shale waste as fine aggregate without any auxiliary modifiers reduced the water stability of asphalt mixtures, the residual stability is 70.21 % after 48 h immersion, which does not meet Chinese requirement of residual stability greater than 75% [36]. Therefore, auxiliary modifiers are needed to improve water stability during application.…”
Section: Oil Shale Waste Powdermentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, shifting pavement engineering toward a more environment-friendly and sustainability industry has brought increased attention [13][14][15][16]. Warm mix asphalt (WMA) technology, as recent innovations in pavement engineering technology, has been appreciated [17,18].…”
Section: Introductionmentioning
confidence: 99%